Resistance as an element of contradictory school culture = Opór jako element kultury szkoły pełnej sprzeczności - Babicka-Wirkus, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article deals with the issue of school culture from the perspective of its inherent resistance. It is a manifestation of a contradictory nature of this culture. The text aims to analyze the oppositional manifestations of school culture located in different dimensions of its activity. Paradoxically, school culture is constructed from contradictions and thus, its full knowledge requires the diagnosis of the dualities that coexist in it. This article analyzes the clash of these dualities in normative, organizational, symbolic, spatial, temporal, aesthetic and interactive dimensions.
Keywords: resistance; school culture; contradiction; opór; kultura szkoły; sprzeczność